Impact of the Brazilian Family Health Strategy on child oral health-related quality of life: a cohort study - Renita Baldo MORAES; Camila Silveira SFREDDO; Thiago Machado ARDENGHI (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Most of the Brazilian population is covered by the Family Health Strategy (FHS), however no longitudinal study has assessed the impact of the FHS on child oral health-related quality of life (OHRQoL). The objective of the study was to evaluate the longitudinal impact of the FHS on the OHRQoL. This study followed up 459 children aged 2 to 5 years for 2 years. OHRQoL was assessed by the Brazilian version of the Early Childhood Oral Health Impact Scale (ECOHIS) at baseline (April to November 2016) and follow-up (April to December 2018). Children's parents answered a questionnaire regarding sociodemographic information, FHS service, and dental service. Participants were clinically examined for dental caries. Multilevel Poisson regression was used to assess the associations between FHS variables at baseline and overall/domain-specific of the ECOHIS scores over time. A total of 365 children were reassessed for OHRQoL (follow-up rate: 79.5%). The absence of FHS coverage from the child's first year of age was associated with higher scores in the family function domain [rate ratio (RR) = 2.42; 95% confidence interval (CI) 1.28-4.58)]. Home visits by the FHS team members were associated with higher psychological domain scores (RR = 1.60; 95%CI 1.01-2.57). Children not covered by the FHS since the first year of age reported worse OHRQoL over time. This fact highlights the importance of an integrated health approach to promote children's health.